Snowball formation for Cs+ solvation in molecular hydrogen and deuterium. Issue 28 (4th July 2019) - Ortiz de Zárate, Josu; Bartolomei, Massimiliano; González-Lezana, Tomás; Campos-Martínez, José; Hernández, Marta I.; Pérez de Tudela, Ricardo; Hernández-Rojas, Javier; Bretón, José; Pirani, Fernando; Kranabetter, Lorenz; Martini, Paul; Kuhn, Martin; et al.
Abstract : Features of the solvation of Cs + by H2 or D2 are unveiled by means of a combined experimental and computational work. Abstract : Interactions of atomic cations with molecular hydrogen are of interest for a wide range of applications in hydrogen technologies. These interactions are fairly strong despite being non-covalent, hence one can ask whether hydrogen molecules would form dense, solid-like, solvation shells around the ion (snowballs) or rather a more weakly bound compound. In this work, the interactions between Cs + and H2 are studied both experimentally and computationally. Isotopic substitution of H2 by D2 is also investigated. On the one hand, helium nanodroplets doped with cesium and hydrogen or deuterium are ionized by electron impact and the (H2 /D2 ) n Cs + (up to n = 30) clusters formed are identified via mass spectrometry. On the other hand, a new analytical potential energy surface, based on ab initio calculations, is developed and used to study cluster energies and structures by means of classical and quantum-mechanical Monte Carlo methods. The most salient features of the measured ion abundances are remarkably mimicked by the computed evaporation energies, particularly for the clusters composed of deuterium. This result supports the reliability of the present potential energy surface and allows us to recommend its use in related systems. Clusters with either twelve H2 or D2 molecules stand out for their stability and quasi-rigid icosahedral structures. However, the first solvation shell involves thirteen or fourteen molecules for hydrogenated or deuterated clusters, respectively. This shell retains its internal structure when extra molecules are added to the second shell and is nearly solid-like, especially for the deuterated clusters. The role played by three-body induction interactions as well as the rotational degrees of freedom is analyzed and they are found to be significant (up to 15% and 18%, respectively) for the molecules belonging to the first solvation shell.